A 3D‐printable device allowing fast and reproducible longitudinal preparation of mouse intestines. Issue 2 (12th April 2022) - DeLucia, Beckey; Samorezov, Sergey; Zangara, Megan T.; Markley, Rachel L.; Osborn, Lucas J.; Schultz, Karlee B.; McDonald, Christine; Claesen, Jan
Abstract: Accurate and reproducible analysis of murine small and large intestinal tissue is key for preclinical models involving intestinal pathology. Currently, there is no easily accessible, standardized method that allows researchers of different skill levels to consistently dissect intestines in a time‐efficient manner. Here, we describe the design and use of the 3D‐printed "Mouse Intestinal Slicing Tool" (MIST), which can be used to longitudinally dissect murine intestines for further analysis. We benchmarked the MIST against a commonly used procedure involving scissors to make a longitudinal cut along the intestines. Use of the MIST halved the time per mouse to prepare the intestines and outperformed alternative methods in smoothness of the cutting edge and overall reproducibility. By sharing the plans for printing the MIST, we hope to contribute a uniformly applicable method for saving time and increasing consistency in studies of the mouse gastrointestinal tract. Abstract : Reproducible analysis of mouse intestinal lumen is key for preclinical models of intestinal cancer and inflammatory bowel diseases. We developed a 3D printable "Mouse Intestinal Slicing Tool" (MIST), and benchmarked it against a commonly used scissors procedure. Using the MIST halved the time to make intestinal preparations and outperformed alternative methods in smoothness of the cutting edge and reproducibility.